The overexpression and prognostic role of DCAF13 in hepatocellular carcinoma - Jianzhong Cao; Pengjiao Hou; Jiemin Chen; Penghui Wang; Wenqin Wang; Wei Liu; Changzheng Liu; Xiaodong He (Tumor Biology, 2017)
DDB1 and CUL4 associated factor 13 (DCAF13) is a protein coding gene located on chromosome 8q22.3, which is a hotspot amplified in various cancers. DCAF13 has been reported to be frequently amplified in breast cancer patients. However, the genetic alteration and potential role of DCAF13 in other cancers, including hepatocellular carcinoma, have not been investigated yet. In this study, we found that DCAF13 was amplified in 14.7% of the cases and its expression was upregulated (p < 0.001) in hepatocellular carcinoma samples in The Cancer Genome Atlas dataset. Increased expression of DCAF13 was also noticed in 40 paired hepatocellular carcinoma and adjacent non-tumor tissues both at messenger RNA and protein levels (p = 0.0002 and 0.0016, respectively). A positive relationship was observed between augmented DCAF13 levels and poorer tumor grade (p = 0.005), and we also found that hepatocellular carcinoma patients with increased DCAF13 expression in their tumors had significantly poorer survival compared with those with decreased DCAF13 expression (median survival time: 45.73 and 70.53 months, respectively). Multivariate Cox regression analysis showed that DCAF13 was an independent prognostic predictor of survival in hepatocellular carcinoma patients. Gene ontology and Kyoto Encyclopedia of Genes and genomes analysis indicated the potential role of DCAF13 as a crucial cell cycle regulator. Collectively, our findings revealed that the overexpression of DCAF13 in hepatocellular carcinoma was significantly associated with poor survival and may participate in the regulation of cell cycle progression.